1996
DOI: 10.1897/1551-5028(1996)015<0986:pcoaim>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes of Aluminium in Mixing Zones: Mortality and Physiological Disturbances in Brown Trout (Salmo Trutta L.)

Abstract: Abstract-A standardized laboratory setup, simulating field mixing zones that originate at the confluence of limed rivers with acidic, aluminium-rich, tributaries, has been developed. Detailed analyses of the chemical speciation of aluminium (Al) in relation to the biological response of brown trout were performed to identify the mechanism of unexpected high fish mortality in the above-mentioned mixing zones with pH levels above 6.0. Brown trout experienced an acute cumulative mortality (98% in 48 h) immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 24 publications
5
38
0
1
Order By: Relevance
“…For example, toxicity has been observed under laboratory conditions when the test solutions were not aged and not at steady state, owing to the existence of more toxic transient Al species [12]. Preliminary tests in our laboratory and others [3,9,10] have shown that aging of test waters for a short period before testing was sufficient for stabilizing toxicity. Gensemer et al [3] concluded that approximately 3 h was sufficient.…”
Section: Importance Of Solution Aging In Toxicity Testing With Aluminummentioning
confidence: 94%
See 2 more Smart Citations
“…For example, toxicity has been observed under laboratory conditions when the test solutions were not aged and not at steady state, owing to the existence of more toxic transient Al species [12]. Preliminary tests in our laboratory and others [3,9,10] have shown that aging of test waters for a short period before testing was sufficient for stabilizing toxicity. Gensemer et al [3] concluded that approximately 3 h was sufficient.…”
Section: Importance Of Solution Aging In Toxicity Testing With Aluminummentioning
confidence: 94%
“…Aluminum represents a challenge for toxicity testing because insoluble hydroxide species can form quickly when pH changes from acidic to relatively circumneutral pH conditions (minutes to a few hours) [9][10][11][12]. Aluminum species can be transformed quickly in ambient waters to more insoluble phases after Al introduction; nevertheless, toxicity has been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this transformation period, the formation of short-lived (i.e., transient) forms of precipitated Al, such as colloidal and amorphous forms, can exist on the scale of a few minutes to hours, whereas more stable crystalline forms can take days to fully form [8]. Studies have shown that the toxicity of test solutions prepared from an acidic Al stock solution decrease considerably the longer they are allowed to age prior to exposure of organisms [9][10][11][12]. Transient species responsible for toxicity of Al are, therefore, unlikely to exist long enough to be a chronic risk to aquatic organisms except in mixing zones, where Al-rich acidic or basic waters meet more neutral waters, leading to continual precipitation of Al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Al accumulation, in addition to injury to the gill epithelium, causes apoptosis and necrosis of gill ion-transporting cells (Eeckhaoudt 1994), which is considered to be the main cause of ion-regulatory and osmoregulatory dysfunction (Witters et al 1996). Fish death following Al exposure is also associated with an inflammatory response to Al-hydroxides with excessive mucous production and subsequent disruption of O 2 and CO 2 diffusion Witters et al 1991).…”
mentioning
confidence: 99%